The significance of Sanskrit names of medicinal plants used in Ayurveda - Leif-Alexander Garbe; Kandace Baez; Vijay J. Tiwari; Fabien Schultz (Medicinal Plant Biology)
In ancient India, seers, sages, and Ayurveda practitioners would name traditional medicinal plants based on their pharmacological activity and scientific observations using Sanskrit, one of the oldest and most sacred languages of the world. In the present study, 23 medicinal plants used in Ayurveda have been analyzed to decipher the real meaning of each Sanskrit name by breaking down each name into its root word(s). The Sanskrit names of each medicinal Ayurveda plant have been cross-checked using a Sanskrit-English dictionary and five other online Sanskrit dictionaries. Each plant species was then placed in one of four categories based on their pharmacological activity. Translating and analyzing the Sanskrit names and relating them to their meaning in modern English, as well to pharmacological reports published on the respective medicinal plants, led to a number of results for each of the 23 species. After carefully analyzing the Sanskrit names, it was concluded that the ancient Indian seers, sages, and Ayurveda practitioners accurately named these 23 medicinal plants based on their bioactive compounds and pharmacological properties. However, further phytochemical and pharmacological investigations are necessary to confirm the uses mentioned within the Sanskrit names of plants.